2019
DOI: 10.1007/s12594-019-1175-z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Hexavalent Chromium using Natural Goethite: Isotherm, Thermodynamic and Kinetic Study

Abstract: This paper examines the potential of natural goethite as an adsorbent for removing Cr(VI) from the aqueous solution through adsorption isotherms, thermodynamics and kinetics study. The study is based on the batch experiments as a function of initial Cr(VI) concentrations, contact time, pH and temperature at fixed solid/solution ratio. The pH has pronounced effect on process of removal and removal is higher in lower pH range, maximum (99.14 %) being at pH 2. The adsorption of Cr(VI) onto goethite is endothermic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The decrease in R L with an increase in the pH indicated that the adsorption was more favorable at higher pH for the Fh-Cr(III) systems and at lower pH for Cr(VI). The values of the parameter R L less than 1 were also obtained by Kar & Equeenuddin (2019) studying the adsorption behavior of Cr(VI) using natural goethite, and Bhattacharya et al (2008) investigating the adsorption of Cr(VI) onto activated alumina.…”
Section: Isotherm Data Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The decrease in R L with an increase in the pH indicated that the adsorption was more favorable at higher pH for the Fh-Cr(III) systems and at lower pH for Cr(VI). The values of the parameter R L less than 1 were also obtained by Kar & Equeenuddin (2019) studying the adsorption behavior of Cr(VI) using natural goethite, and Bhattacharya et al (2008) investigating the adsorption of Cr(VI) onto activated alumina.…”
Section: Isotherm Data Analysismentioning
confidence: 98%
“…As ferrihydrite is an effective barrier to the migration of heavy metal ions in soils and aqueous systems, it can be a potential adsorbent for pollutants uptake in the pH range of most natural waters (Ajouyed et al, 2010). Among the available adsorbents, natural and synthetic iron oxides and (oxyhydr)oxides (Asgari et al, 2008;Campos, 2009;Ajouyed et al, 2010;Adegoke et al, 2014;Shahriari et al, 2014;Kar & Equeenuddin, 2019), including ferrihydrite (Zachara et al, 1987;Tzou, Wang & Loeppert, 2003;Zhu et al, 2010;Pieczara & Rzepa, 2016), were examined for Cr removal.…”
Section: Introductionmentioning
confidence: 99%
“…The sorption isotherms were studied at 23 °C under the conditions mentioned in Sect. 2.3 by varying the initial concentration of Cr(VI) in the aqueous solution (0.25; 0.5; 1 and 1.5 mmol L −1 ) at a fixed equilibrium time of 8 h. All experimental data were fit to linear forms of the Langmuir, Freundlich and Temkin isotherm models (Table 1) [31,33].…”
Section: Sorption Isotherm Studiesmentioning
confidence: 99%
“…The Langmuir isotherm considers that the sorption process occurs with the following: (a) formation of a monolayer on the biosorbent surface of; (b) no interaction between molecules adsorbed on neighbouring locations; and (c) all the sites are identical and energetically equivalent [31,33,68]. The chemisorption is usually explained as this single-layer process.…”
Section: Standardised Effectsmentioning
confidence: 99%
“…For this reason, it is said that there is an energetically heterogeneous distribution of the available active sites for the adsorption of the metal [39][40][41][42]. On the other hand, the value of Freundlich's constant n is in the range 1-10 for Hg (II).…”
Section: Kinetics and Adsorption Isothermsmentioning
confidence: 99%